In search of a causal relationship between industrial output and employment in Ireland - Fell, John P.C. (Economic & Social Studies, 1989)
Recently, many analysts of the Irish manufacturing sector have been concerned with an apparent negative relationship, between aggregate industrial employment and output in Ireland, that has developed since 1980. Over the period 1980 to 1987, industrial output increased by almost 50 per cent while industrial employment declined by about 20 per cent over the same period. This experience contrasts sharply with the period 1976 to 1980 when industrial output rose by 24 per cent and employment rose by 10 per cent. An explanation often implied for this apparent negative relation is the composition of aggregate industrial output between "Modern" and "Traditional" sectors (see Baker (1988)).
Keywords: Industrial output; Employment; manufacturing sector; Ireland